2019
DOI: 10.1155/2019/7891746
|View full text |Cite
|
Sign up to set email alerts
|

Serum Nickel and Titanium Levels after Transcatheter Closure of Atrial Septal Defects with Amplatzer Septal Occluder

Abstract: Introduction There is a concern about release of nickel and titanium after implantation of nitinol-containing devices. Objective To evaluate serum nickel and titanium release after implantation of Amplatzer occluder. Materials and methods In 38 pediatric patients with no history of nickel sensitivity, blood samples were drawn 24 hours before and 24 hours, 1, 3, 6, and 12 months after implantation. Nickel and titanium concentrations were measured by atomic absorption spectrophotometry. Results The median serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…[ 22 ] The present results showed no increased serum levels of nickel after parylene-coated device implantation in the trial group, while implantation of the traditional device in the control group resulted in significantly increased serum levels of nickel at 2 weeks and a peak value at 1 month after implantation before gradually decreasing to baseline levels during follow-up, which was consistent with previous studies. [ 12 14 ] These results suggest that the parylene-coated ASD occluder has the potential to prevent nickel release after device implantation, and may be a viable alternative for patients with ASD, especially those with nickel allergy.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…[ 22 ] The present results showed no increased serum levels of nickel after parylene-coated device implantation in the trial group, while implantation of the traditional device in the control group resulted in significantly increased serum levels of nickel at 2 weeks and a peak value at 1 month after implantation before gradually decreasing to baseline levels during follow-up, which was consistent with previous studies. [ 12 14 ] These results suggest that the parylene-coated ASD occluder has the potential to prevent nickel release after device implantation, and may be a viable alternative for patients with ASD, especially those with nickel allergy.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have demonstrated evidence of nickel release after nitinol-containing occluder implantation [12–14] . Ries et al [12] reported a significant rise in serum nickel levels after the Amplatzer device implantation; the mean serum levels of nickel were significantly increased at 24 h and reached the peak value at 1 month after implantation, before gradually decreasing to the baseline level.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Percutaneous ASD closure using Nitinol devices can be carried out safely without any significant ill effects related to nickel release. In another study by Elkiran et al [78] it was examining the serum nickel and titanium release after transcatheter implantation of Amplatzer device used. In 38 pediatric patients with no history of nickel sensitivity, blood samples were drawn 24 hours before and 24 hours, 1, 3, 6, and 12 months after implantation of Amplatzer occluder.…”
Section: In Vivo Metal Ion Release From Metallic Vascular Devicesmentioning
confidence: 99%